Targeting GGT1 Eliminates the Tumor-Promoting Effect and Enhanced Immunosuppressive Function of Myeloid-Derived Suppressor Cells Caused by G-CSF - Xie, Zhiqi; Kawasaki, Takahiro; Zhou, Haoyang; Okuzaki, Daisuke; Okada, Naoki; Tachibana, Masashi (Frontiers in Pharmacology, 2022)
Myeloid-derived suppressor cells (MDSCs) are major immunosuppressive cells that accumulate in tumor-bearing hosts. Since MDSCs suppress anti-tumor immunity and promote tumor progression, they are promising targets for cancer immunotherapy. Granulocyte colony-stimulating factor (G-CSF) is an agent used for the treatment of chemotherapy-induced febrile neutropenia (FN) in patients with cancer. However, several reports have revealed that G-CSF plays crucial immune-related adverse roles in tumor progression through MDSCs. In this study, we showed that MDSCs differentiated in the presence of G-CSF in vitro exhibited enhanced proliferation and immunosuppressive activity compared to those differentiated without G-CSF. RNA sequencing analysis demonstrated that G-CSF enhanced the immunosuppressive function of MDSCs by upregulating gamma-glutamyltransferase (GGT) 1. Moreover, in the EL4 lymphoma-bearing neutropenic mouse model, administration of recombinant G-CSF increased the number of MDSCs and attenuated the anti-cancer effect of chemotherapy. We showed that the combination of GGsTop, a GGT inhibitor, could prevent G-CSF-induced tumor growth, without affecting the promotion of myelopoiesis by G-CSF. These results suggest that targeting GGT1 on MDSCs can eliminate the tumor-promoting effect of G-CSF. Furthermore, GGsTop could be an attractive combination agent during G-CSF treatment for FN in patients with cancer.